Exploiting the microbiota of organic and inorganic acid-treated raw poultry products to improve shelf-life - Dittoe, Dana K.; Feye, Kristina M.; Ovall, Christina; Thompson, Hayley A.; Ricke, Steven C. (Frontiers in Microbiology, 2024)
Targeted amplicon sequencing of the 16S rRNA delineates the complex microbial interactions that occur during food spoilage, providing a tool to intensively screen microbiota response to antimicrobial processing aids and interventions. The current research determines the microbiota and spoilage indicator (total aerobes and lactic acid bacteria; LAB) response to inorganic and organic antimicrobial intervention use on the shelf-life of fresh, never-frozen, skin-on, bone-in chicken wings. Wings (n=200) were sourced from local processor and either not treated (NT) or treated with 15-s dips of tap water (TW), organic (peracetic acid; PAA), inorganic acids (sodium bisulfate; SBS), and their combination (SBS + PAA). Wings were stored (4°C) and rinsed in neutralizing Buffered Peptone Water (BPW) for 1 min on d 0, 7, 14, and 21 post-treatment. Spoilage indicators, aerobic mesophiles and LAB, were quantified from rinsates. Genomic DNA of d 14 and 21 rinsates were extracted, and V4 of 16S rRNA gene was sequenced. Sequences were analyzed using QIIME2.2019.7. APC and LAB counts were reported as Log10 CFU/g of chicken and analyzed in R Studio as a General Linear Model using ANOVA. Pairwise differences were determined using Tukey's HSD (P£0.05). Spoilage was indicated for all products by day 21 according to APC counts (>7 Log10 CFU/g); however, wings treated with SBS and SBS + PAA demonstrated a 7-day extended shelf-life compared to those treated with NT, TW, or PAA. The interaction of treatment and time impacted the microbial diversity and composition (P < 0.05), with those treated with SBS having a lower richness and evenness compared to those treated with the controls (NT and TW; P<0.05, Q<0.05). On d 14, those treated with SBS and SBS + PAA had lower relative abundance of typical spoilage population while having a greater relative abundance of Bacillus spp. (~70 and 50% of population; ANCOM P < 0.05). By d 21, the Bacillus spp. populations decreased below 10% of the population among those treated with SBS and SBS + PAA. Therefore, there are differential effects on the microbial community depending on the chemical intervention used with organic and inorganic acids, impacting the microbial ecology differently.